An Optimized Technique for Chain Head Selection in Pegasis Protocol for WSN - Srivastava, Suraj; Grover, Dinesh (International Journal of Computer Sciences and Engineering, 2018)
Wireless Sensor Network (WSN) consists of sensor nodes which sense, process and transmit information. The most important parameter that is of great significance in a sensor network is its lifetime. In this research work, an optimized technique for chain head selection in Pegasis protocol has been proposed on the basis of genetic algorithm, gravitational search algorithm and fuzzy logic. Experimental results indicate that the proposed approach results in significant reduced energy consumption thereby enhancing the network lifetime.